A Community-Based Walk-In Screening of Depression in Taiwan - Shu-Yu Tai; Tzu-Chiao Ma; Ling-Chun Wang; Yuan-Han Yang (The Scientific World Journal)
Depression is a crucial public health problem because of its relatively high association with suicidal attempts, prolonged social isolation, poor physical health, and dementia. However, the available data and study on the prevalence of depression in Taiwan were mostly completed within the previous 1 to 2 decades, and these studies were limited to certain areas or populations. Little is known regarding the current status of depression in Taiwan. We used a brief tool, the Center for Epidemiological Studies Depression Scale (CES-D), to screen depression in 4 areas among the general and aged population. The results showed a higher CES-D score in the southern area among general (mean ± SD: 7.8 ± 8.4) or aged participants (mean ± SD: 7.2 ± 8.0) compared with other areas. The ratio of suspected depression patients was 16.4% of all recruited participants and 13.3% of aged participants. These results may provide information for this public health issue.